Prenatal diagnosis of interrupted aortic arch and oesophageal atresia – monitoring and postnatal management with positive outcome – case report - Biały, Łucja H.; Sylwestrzak, Oskar; Maroszyńska, Iwona; Piaseczna-Piotrowska, Anna; Grzelak, Piotr; Moszura, Tomasz; Januszewska, Katarzyna; Malec, Edward (Prenatal Cardiology, 2023)
This paper presents a rare case of a fetus with more than one “lethal” malformation complex heart defect: interrupted aortic arch (IAA) with atrio-ventricular canal, oesophageal atresia, and agenesis corpus callosum. Prenatal diagnosis allowed for transfer in utero, and fetal echocardiography longitudinal monitoring to confirm fetal well-being and to avoid prematurity. Delivery happened in a tertiary centre, and there was an early postnatal surgery: on the 2nd day a successful thoracoscopic repair of the oesophagus was done, and on the ninth day binding of both pulmonary arteries was set up. Despite the poor prognosis at the time of prenatal detection of malformations, our patient was discharged home after a 54-day hospital stay, in good postnatal clinical condition. It is the first case from our unit dealing with congenital malformations presenting a fetus and neonate who required 2 surgeries early after birth (thoracoscopy for oesophageal repair and palliative cardiac surgery – binding of pulmonary arteries) with positive outcome, representing a milestone for prenatal malformations from the perspective of a tertiary centre.